Familiarity with radiation exposure dose from diagnostic imaging for acute pulmonary embolism and current patterns of practice. Issue 5 (September 2014) - Ahn, Justin S.; Edmonds, Marcia L.; McLeod, Shelley L.; Dreyer, Jonathan F.
ABSTRACT: Objective: To assess the current level of knowledge and practice patterns of emergency physicians regarding radiation exposure from diagnostic imaging modalities for investigating acute pulmonary embolism (PE). Methods: An online survey was sent to adult emergency physicians working at two academic tertiary care adult emergency departments (EDs) to determine imaging choices for investigating PE in various patient populations and to assess their current knowledge of radiation doses and risks. A retrospective chart review was performed for all adult patients who underwent computed tomographic pulmonary angiography (CTPA) and/or ventilation-perfusion (V/Q) scanning in the same EDs. Results: The survey response rate was 72.1% (31 of 43 physicians). For patients < 30 years old, 83.9% of physicians chose V/Q scanning as their test of choice, regardless of gender. Although only a third of respondents knew the estimated radiation dose of a V/Q scan (37.5%) and a CTPA (32%), the majority were aware that V/Q scans involved less ionizing radiation than CTPAs. In the retrospective review, 663 charts were reviewed, including 201 CTPAs and 462 V/Q scans. V/Q scanning was the preferred modality in female patients (75.9% v. CTPA 24.1% [OR 2.1; 95% CI 1.5–2.9]) and in patients < 30 years old (87.9% v. CTPA 12.1% [OR 4.8; 95% CI 2.4–9.4]). Conclusions: Although surveyed physicians possessed limited knowledge of radiation doses of CTPA and V/Q scans, they preferentially used the lower radiation V/Q scans in younger patients, particularly females, in both the survey vignettes and in clinical practice. This may reflect efforts to reduce radiation exposures at our institution.